REFORMASI PENDIDIKAN ISLAM: UPAYA MEMBANGUN KONSEP PENDIDIKAN ISLAM MODERN DI INDONESIA - Iroh Suhiroh; Wawan Wahyudin; Ade Fakih Kurniawan (Journal of Innovation Research and Knowledge, 2022)
This article will explain about Islamic education reform in an effort to build the concept of modern Islamic education in Indonesia. Islamic education reform itself aims to make Islamic education run effectively and efficiently, dynamically, able to respond to technological developments and advances. Various Indonesian government policies in the form of laws and government regulations indicate their support and desire to empower the people through the provision of superior education in order to achieve national education goals. This is evidenced by the stipulation of standards for content, process, competency of graduates, educators and education staff, facilities and infrastructure, financing management and assessment system. Education is expected to be able to overcome the moral and personal problems of the nation's children. Islamic education in Indonesia is considered still trapped in a disputed issue, the transformation of knowledge and religious values ​​is still low, so that sometimes they forget the reality of work needs